Procyclidine Use with Long-Acting Injectable Antipsychotics - Prabin Gautam; Titilola Osoba; Shalina Mitchell (BJPsych Open)
Aims: Our aim was to review if procyclidine is being prescribed as per BNF guidelines at DGS CMHT. As per BNF guidelines, procyclidine is recommended to be initiated at 2.5 mg of procyclidine three times per day increasing by 2.5 mg daily until symptoms are relieved. The effective maintenance dose is usually 10–30 mg procyclidine per day. After a period of 3–4 months of therapy, procyclidine should be withdrawn and the patient should be observed to see whether the neuroleptic-induced extrapyramidal symptoms recur.